ANALISIS KONSTRASTIF FONEM BAHASA KANUM SOTA DAN BAHASA KANUM BARKARI - Yohanis Sanjoko (Kibas Cenderawasih : Jurnal Ilmiah Kebahasaan dan Kesastraan, 2019)
This article disscusses about the phoneme comparison of Kanum Sota language with Kanum Barkari’s . Language of Kanum Sota and Kanum Barkari as the vernacular languages in the province of Papua, which are spoken by people in the District of  Sota and the District of Naukenjerai, Merauke Regency. Kanum Sota language and Kanum Barkari language situated in the border between Indonesia and Papua New Guinea. The purpose of this paper is  to describe and compare the phonological system of Kanum Sota language with Barkari Kanum language. This study was conducted through literature. Data analysis was conducted by describing and comparing the soundssystem, phonemes, and phonemes distribution of Kanum sota language with Kanum Barkari language. The results of this study shows that Kanum Sota has more consonant phonemes than Barkari Kanum language. The similarity of  consonant phonemes of Kanum Sota language and Kanum Barkari language is the phoneme /p/, /b/, /t/, /d/, /j/, /k/, /g/, /m/, /n/, /ŋ/, /l/, /s/, /r/, /h/, /w/, and /y/. Consonant phonemes that owned by Kanum Sota language but it is not owned by Barkari Kanum language is the phoneme /c/, /ñ/, and /f/. Both of these language have six vowel phonemes. The similarity of  vowel phonemes between Kanum Sota and Kanum Barkari is  the phoneme /a/, /i/, /e/, and /u/. Vowel phonemes that owned by Kanum Sota language but it is not owned by Barkari Kanum language is the phoneme /ә/ and /ↄ/. While vowel phonemes that owned by Kanum Barkari language but it is not owned by Sota Kanum language is the phoneme /є/ and /o/.